Marketing Strategy for Cibaduyut UKM Craftsmen Shoes During the Covid-19 Pandemic - Muttaqin, Rizqi; Saputera, Denny; Dewi, Rina Ariyanthi; Moenardy, Dwi Fauziansyah; Santoso*, Rizal Budi; Alam, Gilang Nur (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This article aims to explain the marketing strategy for MSME shoemakers in the Cibaduyut area during the Covid-19 pandemic. The purpose of this study was to determine the effect of the Covid-19 pandemic on MSMEs shoe craftsmen in the Cibaduyut area and the efforts of these MSMEs in utilizing digital platforms to maintain their business during the Covid-19 pandemic. The research method uses qualitative methods through interviews and observation as well as literature and data reduction. This research shows the challenges faced by MSMEs in utilizing digital platforms and provides recommendations for improving marketing strategies so that MSMEs can utilize digital platforms more effectively. Keywords: Cibaduyut; Mix Marketing; MSME; Shoesmakers; Marketing Strategy